Transformasi Proteksi Tegangan: Sistem Monitoring IoT untuk Pemantauan Real-Time - Agus Kiswantono (DIELEKTRIKA, 2024)
Electric energy is a vital resource extensively used in various sectors such as industry, offices, agriculture, and trade. Its significance in supporting a nation's economy is undeniable, making the monitoring of power consumption and quality crucial. This study focuses on designing and implementing an Internet of Things (IoT)-based monitoring system for overvoltage protection in an electrical power system. The power system incorporates an Over Voltage Relay (OVR) as a protective measure against voltage fluctuations that may harm the equipment. The OVR operates based on electromagnetic principles, promptly responding to deviations in voltage beyond specified limits. Additionally, the system integrates the PZEM-004T module for measuring voltage, current, power, frequency, energy, and power factor, providing comprehensive insights into the electrical system's performance. The heart of the IoT-based monitoring system is the ESP32-32D module, facilitating real-time monitoring and remote control through the Blynk application. The implemented system successfully detects overvoltage conditions, automatically triggers protective measures, and allows users to monitor the power system through an intuitive interface.The study concludes with an evaluation of the average voltage measured by the OVR, emphasizing the system's reliability and potential for further industrial applications. The average OVR voltage, determined to be approximately 239 Volts, provides a comprehensive overview of measurement consistency throughout the experiments. This research contributes to the enhancement of electrical power management, ensuring the reliability and efficiency of overvoltage protection through IoT-based monitoring systems. Further evaluations and advancements could optimize the system's performance for broader industrial applications.